EKOLOGI SPIRITUAL MADRASAH, MOTIVASI IBADAH, DAN RESILIENSI BELAJAR SISWA - Didit Darmawan; Bonafid Ikrom (Consilium: Education and Counseling Journal, 2026)
This study conducts a literature review on the influence of the madrasah's religious school environment on students' worship motivation and discipline, and how these elements serve as a foundation for Islamic Education learning outcomes and strengthen learning resilience. Using a qualitative library research approach, this study analyzes relevant academic sources to construct a conceptual synthesis. The findings indicate that the spiritual ecology of madrasah shapes students' spiritual awareness through habituation, role modeling, and value internalization. This awareness fosters intrinsic worship motivation and authentic self-discipline, which are crucial for achieving meaningful Islamic Education outcomes beyond mere cognitive mastery. Furthermore, worship motivation provides inner peace and a life orientation that transcends academic achievements, enabling students to reframe difficulties as opportunities for growth. Worship discipline cultivates self-control, time management, and consistency essential for academic persistence. Both variables function as psychological resources that bolster students' resilience in navigating competitive school environments. The study concludes that a well-designed spiritual ecology in madrasah is not merely an emblem of Islamic identity but a strategic foundation for developing resilient learners capable of achieving maximum learning outcomes while maintaining spiritual integrity. These findings imply the need for systematic integration of spiritual development with academic capacity building in madrasah policies and practices.